2020
DOI: 10.1111/cogs.12881
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Interplay of Semantics and Phonology During Failures of Word Retrieval by People With Aphasia Using a Multiplex Lexical Network

Abstract: Investigating instances where lexical selection fails can lead to deeper insights into the cognitive machinery and architecture supporting successful word retrieval and speech production. In this paper, we used a multiplex lexical network approach that combines semantic and phonological similarities among words to model the structure of the mental lexicon. Network measures at different levels of analysis (degree, network distance, and closeness centrality) were used to investigate the influence of network stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 77 publications
(142 reference statements)
1
45
0
Order By: Relevance
“…In multiplex networks there may be a network of phonologically related words connected to another network layer in which the words are connected by edges if they are semantically related. Such networks have been used to examine a number of language phenomena, including the word-finding difficulties of people with aphasia (e.g., [36]).…”
Section: Discussionmentioning
confidence: 99%
“…In multiplex networks there may be a network of phonologically related words connected to another network layer in which the words are connected by edges if they are semantically related. Such networks have been used to examine a number of language phenomena, including the word-finding difficulties of people with aphasia (e.g., [36]).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive networks need not be limited—such as the phonological network examined in [ 14 ]—to one type of representation or information. Work on multilevel networks, which enable researchers to look at, for example, a network of words with phonological relationships overlayed on a network of words with semantic relationships have increased our understanding of word-learning in children [ 53 ], and of acquired language disorders in adults [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, this was the approach of Castro et al. (2020), who identified specific network structure measures that influenced picture naming by persons with aphasia. While their study only provided a verbal account of how structure and process interacted, simulations conducted on the proposed language network could be used to further substantiate these claims.…”
Section: Methodological Limitations With Clinical Datamentioning
confidence: 99%
“…For example, phonological and orthographic networks place links between words if they differ by a certain number of phonemes/letters (e.g., one phoneme/letter difference through addition, substitution, or deletion). This network approach has shown that greater consideration of the structure of words in memory is necessary for a complete understanding of a variety of language processes (e.g., Beckage & Colunga, 2015; Vitevitch, 2008; Vitevitch, Chan, & Goldstein, 2014), including word retrieval (Castro & Stella, 2019; Castro, Stella, & Siew, 2020; Chan & Vitevitch, 2010; Vitevitch & Castro, 2015; Vitevitch, Goldstein, Siew, & Castro, 2014; Vitevitch & Sommers, 2003).…”
Section: Network Model To Study Word Retrievalmentioning
confidence: 99%
See 1 more Smart Citation